Educação ambiental e gestão de resíduos sólidos: práticas educativas no Centro Municipal de Educação Infantil Carlos Gauto, Foz do Iguaçu - PR - Schmitz, Waleska Claire (2015)
This work has the theme the environmental education in early childhood education. It's treat about the importance and ways of include environmental education in children's daily lives, looking for through methodology adapted to the age range of students, teach and assess the knowledge about separation of waste and other topics of environmental education and the environment. Studies show that the environmental education is important to raise awareness of people about the worldin where they live so they can have more quality of life without disrespect the environment. The most important objective of this work is to make the students have a new mindset regarding how to use of the resources offered by nature, thus creating a new behavior, seeking a balance between man and the environment. It was found through this study that environmental awareness is necessary already in the early school years, especially to the educators as they have great responsibility in the training citizen of their students, it is important that the students can take understanding about what happens and what they can do to preserve the environment, and disseminate this knowledge to the society.